PERAN KREDIT MODAL USAHA BAITUL MAAL WAT TAMWIL (BMT) DALAM PENINGKATAN PENDAPATAN RUMAH TANGGA MISKIN DESA MOTONG - Didi Suwardi; Fitriah Permata Citra (Valid: Jurnal Ilmiah, 2018)
The formulation of the problem in this research is whether the provision of capital credit business BMT can play a role in increasing the income of poor households in Motong Village Utan District. The main objective of this research is to analyze the role of business credit in increasing the income of poor households after obtaining the capital credit of BMT business in Motong Village. The method used is descriptive method. This research was conducted in BMT Motong Village, Utan, Sumbawa District. The types and sources of research data are primary and secondary data. Data Collection Method uses interviews, questionnaires and techniques of documentation. Population and Sample The total population in this study are as many as 168 BMT customers and the number of samples totaling 63 BMT customers. The analytical technique uses the income formula and the wilcoxon rank test statistic. The results showed that the amount of capital owned before the capital credit business ranged from Rp.350.000 to Rp.2.650.000 / month with an average of Rp.1.177.778 and the amount of income ranges from Rp.145,328 to Rp.6,462,624 with an average of Rp.2,600,779 and the amount of capital held after the capital credit business ranges from Rp.850,000 to Rp.4.650.000 / month with an average of Rp.2.755.556 total revenues ranged from Rp.726.020 to Rp.9.058.756/ month with an average of Rp.3.803.203, has a difference amount of Rp.1.202.424, This condition shows that the provision of capital credit of BMT businesses to poor households can increase the income of poor households. In the statistical test, the rank of wilcoxon indicates the overall value of Asymp sig 0.000 ≤ 0.05 or Zhitung of -894 is in critical area Ztabel ≤ 1.645 or Z ≥ -1,645, so Ho is rejected, while HI accepted. The consequences of HI are accepted and Ho has rejected means two variables have different median values. The hypothesis that there is a difference in income after the capital of business credit was given, proven. The difference is caused by capital, income and business capital credit factors